Strategi Inklusif Pendidikan Agama Islam Terhadap Masyarakat Multikultural - Andre Febrianto; Munir Munir; Karoma Karoma (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research highlights the importance of a social justice-based approach and recognition of diversity in creating an inclusive religious education environment. Values ​​such as tolerance, mutual respect and empathy need to be taught in the curriculum. This research uses a qualitative method with a library study approach, researchers use trusted scientific journal databases such as JSTOR, Google Scholar, and Scopus as the main data source. Through the process of searching and analyzing the literature, researchers were able to identify various inclusive strategies that have been implemented in Islamic religious education. Apart from that, data analysis was also carried out by grouping information based on themes that emerged from related literature. Training for educators to manage diverse classes. Collaboration between schools, families and communities is key in creating a friendly educational environment for all individuals. However, there are still obstacles related to resistance to diversity. Broader education and understanding is needed to increase inclusion in religious education. It is hoped that this research can help develop education policies that are more inclusive and responsive to cultural diversity.